KAJIAN PENGELOLAAN SUMBERDAYA PERAIRAN DI DANAU TEMPE BERBASIS KEARIFAN LOKAL - Razak, A. Rosdianti; Sambu, Haris; Anwar, Asni; -, Burhanuddin (Jurnal Ilmiah Ecosystem, 2020)
This research aims to improve environmental preservation through local wisdom that is owned by the people around Lake Tempe. The research method uses social research methods with qualitative descriptive analysis, with an inductive pattern so that abstracts and conclusions can be drawn and describes a model of marine resource management with the community in the past which conditions with advantages and possible drawbacks. The results showed that the management and utilization of water resources based on local wisdom in Lake Tempe were constrained by aspects of environmental quality degradation, aspects of human resources, aspects of control and technology. For this reason, efforts that can be made include; Increasing conservation efforts, for example planting trees by making effective the relationship between local wisdom of the Bugis community in the upstream area; Increase community participation and fisherman institutions that function as supervisors in maintaining the sustainability of marine resources; Developing a contemporary lake tourism area that features miniature maccera tappareng activities; Increase the capabilities and skills of the Lake Tempe fishing community, so that they can take advantage of existing natural resources, for example increasing the processing and utilization of water hyacinth so that it can become the center of the water hyacinth handicraft industry. Meanwhile, the implications of managing marine resources based on local wisdom have a very positive impact on ecological, economic and social aspects.